RISK FACTORS FOR DEVELOPMENT OF DISSEMINATED FORMS OF INTRUSIVE CANDIDIASIS AMONG CHILDREN SUFFERING FROM BURNS - A.S. Kolbin (Union of pediatricians of Russia, 2006)
The aim of the study is to identify the significant factors for the risk of candidemia development among children, suffering from burns. The authors have conducted an analytical retrospective controlling study. It shows that statistically significant factors the risk of candidemia development among children with major heat injury (burns of III-IV degree) were the area of the full? Thickness burn over 40% (or boundless, p = 0,008); use of car bapenem class antibiotics (or 0,16 with 95% confidence interval 0,08-0,36, p = 0,023); glycopeptids (or 0,13 with 95% confidence interval 0,05-0,33, p = 0,008); mucosa colonization of the upper respiratory tracts with сandida SPP (or 0,14 with 95% confidence interval 0,06-0,32, p = 0,011). Among patients with the above listed factors for the risk of candidemia development it is necessary to conduct prophylaxis by systemic antimicotics, such as: lipid associated forms of amphotericin в and fluconasol.Key words: children, burns, intrusive candidiasis, risk factors.